Stres menurut sarjana barat dan Islam - Noor Izzati Mohd Zawawi; Fariza Md.Sham; A’dawiyah Ismail (Penerbit Universiti Kebangsaan Malaysia, 2019)
Stress is a psychological symptom caused by a number of factors such as biological, medical, psychological and social. It can happen to individuals regardless of age or gender. A person in a state of stress may experience some symptoms such as anxiety, fear, shortness of breath and so on. Hence, this article aims to analyze the similarities and differences of stress from an Islamic and Western perspective. Qualitative research methods are used by performing document analysis on past stress-related studies. The results show that personality and perceptions determine a person's level of stress. Western stress experts like Hans Salye and Lazarus have concluded that extreme stress can be harmful to themselves. But simple stress can motivate one to succeed. Studies have also found that Islamic scholars such as al-Ghazali have assumed that stress is a psychological symptom usually experienced by those who have lost their relationship to Allah Almighty in addition to impure heart. This is because according to al-Ghazali, the personality of an individual depends on his relationship with Allah Almighty and his relationship with humanity. The result of the study found that the greatest difference between Western scholars and Muslims in discussing stress is that Islamic scholars have made the Quran and the Sunnah a major reference in each of their studies as well as empirical studies. On the other hand, Western scholars rely solely on empirical studies. However, in recent times the combination of psychology between Islam and the West has created a holistic and effective approach with a variety of methods of coping and preventing stress that can be applied either generally or using Islamic psychology.